Reply to Correspondence on "Synergy and Antagonism between Allosteric and Active‐Site Inhibitors of Abl Tyrosine Kinase". (25th October 2022) - Johnson, Taylor K.; Bochar, Daniel A.; Vandecan, Nathalie M.; Furtado, Jessica; Agius, Michael P.; Phadke, Sameer; Soellner, Matthew B.
Abstract: Manley and co‐workers provide data demonstrating that, at super‐pharmacological concentrations (300 μM), a ternary complex between Abl, asciminib, and ATP‐competitive inhibitors is possible. The work in our manuscript concerns the interplay of asciminib (and GNF‐2) with ATP‐competitive inhibitors at pharmacologically relevant concentrations ( C max =1.6–3.7 μM for asciminib). Manley and co‐workers do not question any of the studies that we reported, nor do they provide explanations for how our work fits into their preferred model. Herein, we consider the data presented by Manley and co‐workers. In addition, we provide new data supporting the findings in our Communication. Asciminib and ATP‐competitive inhibitors do not simultaneously bind Abl at pharmacologically relevant concentrations unless the conformation selectivity for both ligands is matched. Abstract : At pharmacologically relevant concentrations, asciminib and clinical adenosine triphosphate (ATP) kinase inhibitors cannot simultaneously bind to Abl kinase. Manley and co‐workers correspond that at saturating concentrations (i.e., concentrations that are not achievable in a human), asciminib and dasatinib can simultaneously bind to Abl kinase.